PEMETAAN DAERAH RAWAN KERUSAKAN AKIBAT GEMPA BUMI DI WILAYAH KOTA PALU TAHUN 2000-2018 BERDASARKAN NILAI PERCEPATAN TANAH MAKSIMUM - Saputra, Ary Rhamadan; Djayus, Djayus; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Abstract Palu is the city passed by the Palu-Koro active fault so that tectonic earthquakes often occur, some of which are followed by tsunamis, liquefaction and soil movements. The purpose of this research is to determine the value of peak ground acceleration based on earthquake data from 2000-2018 and to find out areas prone to earthquake damage based on the value of peak ground acceleration in the city of Palu. The data in this research are historical data of earthquakes from 2000-2018 with magnitudes 4.5-9 on the Richter scale and depths of 0-70 Km from USGS (United States Geological Survey) as much 9 data. Earthquake data is processed using empirical equation model Mc. Guirre K. and Donovan to get the value of peak ground acceleration at each specified observation point (grid) by the boundary area 0o37’ LS - 0o58’ LS dan 119o45’ BT - 121o3’ BT. The value of Peak Ground Acceleration at each observation point is processed using software for mapping to get the mapping results. Results of the research, the value of Peak Ground Acceleration in the city of Palu was based on earthquake data from 2000-2018 with Mc. Guirre R.K model ranging from 105,442 - 108,899 gal while the Donovan model ranging from 112,832 - 116,585 gal. The level of earthquake damage in the city of Palu from the highest to the lowest in sequence, namely the districts of North Palu, Tawaeli, Mantikulore, East Palu, Ulujati, West Palu, South Palu and Tatanga.